2013
DOI: 10.18388/abp.2013_1998
|View full text |Cite
|
Sign up to set email alerts
|

Norway spruce (Picea abies) genetic transformation with modified Cry3A gene of Bacillus thuringiensis.

Abstract: Modified versions of the Cry3A gene of Bacillus thuringiensis (Bt) were transferred into Norway spruce (Picea abies). Both the biolistic approach and Agrobacterium tumefaciens mediated procedure were employed for transformation of embryogenic tissue (ET) cultures. The latter method proved to be more efficient yielding 70 transgenic embryogenic tissue lines compared with 18 lines obtained by biolistics. The modified Cry3A genes were driven by a 35S promoter and the nptII screenable selection marker gene was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, transgenic rapeseed containing the Cry1Ac gene can control diamondback moth, hairy bug, and cotton bollworm [ 19 ], and transgenic pigeon bean containing the Cry2Aa gene is resistant to pod borers [ 20 ]. The Cry3A gene in transgenic spruce showed toxicity to spruce bark beetles, indicating that Bt and its toxin proteins add significant value to biological control [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic rapeseed containing the Cry1Ac gene can control diamondback moth, hairy bug, and cotton bollworm [ 19 ], and transgenic pigeon bean containing the Cry2Aa gene is resistant to pod borers [ 20 ]. The Cry3A gene in transgenic spruce showed toxicity to spruce bark beetles, indicating that Bt and its toxin proteins add significant value to biological control [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bt toxins are also being used in generating trangenic crops effectively control crops pests such as CryIAc in rapeseed to control hairy bugs, diamondback moths, and cotton bollworms [87]. Cry2Aagene in transgenic pigeon beans to control pod borers [88], Cry3A gene in transgenic spruce to control bark beetles [89]. According to a recent report, a significant change in the amount of herbicides and pesticide application was observed in the USA with the adoption of herbicides tolerant GM plants [90], such as; transgenic soybean [91], summer corn and cotton.…”
Section: Transgenic Approaches For Environmental Protectionmentioning
confidence: 99%
“…Currently, several reports concerning the genetic transformation of P. abies embryogenic cultures are available [133][134][135][136]. Most studies were carried out on embryogenic tissues using Agrobacterium tumefaciens-mediated transformation.…”
Section: Se-the Future Of Forestry? 61 Applied Biotechnology and Sementioning
confidence: 99%
“…For example, Wenck et al [133] obtained over 100 transformed embryogenic cell lines after their co-cultivation with Agrobacterium strains containing additional copies of virulence genes (either a constitutively active virG or extra copies of virG and virB, both from pTiBo542). Additionally, Briža et al [136] reported 70 transgenic lines, which were transformed with Agrobacterium tumefaciens. In this experiment the modified versions of Cry3A gene of Bacillus thuringiensis, with the increased toxicity against spruce bark beetle, were introduced into embryogenic tissues.…”
Section: Se-the Future Of Forestry? 61 Applied Biotechnology and Sementioning
confidence: 99%